Neurogastronomy: Factors Affecting the Taste Perception of Food - Pelin Tokat; Ilkay Yilmaz (International Journal of Gastronomy Research)
Neurogastronomy is a new formation that includes many researches to provide a connection between gastronomy and neurology. The existence of biological, emotional and cultural factors as flavor in the brain can be explained as neurogastronomy. The data received with the five senses are collected in the brain and perceived in its relevant parts. Research on what kind of perception is created with the formation of missing sensory data in the brain has been increasing day by day. In addition, by considering the different reflections of sensory data from reality, it is examined how they lead to perceptions in the brain. Plate design is very important in terms of visual presentation. What kind of an effect the presentation types of plate design have on customers and what kind of plate design they prefer is a matter of curiosity for researchers. Every stage of life continues in the light of technological developments. One of these technological developments is virtual reality. With the use of virtual reality in the field of neurogastronomy, it is possible to simulate the senses differently. This situation creates the possibility of causing different perceptions in the brain. In this study, neurogastronomy, the concepts of taste and flavor and the parameters affecting the perception of taste were addressed, the studies on the effect of plate presentation and atmosphere were examined, and information was conveyed by making a comprehensive literature review.